A Review of the Current Knowledge of Thermal Stability of Anthocyanins and Approaches to Their Stabilization to Heat - Simona Oancea (MDPI AG, 2021)
Anthocyanins are colored valuable biocompounds, of which extraction increases globally, although functional applications are restrained by their limited environmental stability. Temperature is a critical parameter of food industrial processing that impacts on the food matrix, particularly affecting heat-sensitive compounds such as anthocyanins. Due to the notable scientific progress in the field of thermal stability of anthocyanins, an analytical and synthetic integration of published data is required. This review focuses on the molecular mechanisms and the kinetic parameters of anthocyanin degradation during heating, both in extracts and real food matrices. Several kinetic models (Arrhenius, Eyring, Ball) of anthocyanin degradation were studied. Crude extracts deliver more thermally stable anthocyanins than purified ones. A different anthocyanin behavior pattern within real food products subjected to thermal processing has been observed due to interactions with some nutrients (proteins, polysaccharides). The most recent studies on the stabilization of anthocyanins by linkages to other molecules using classical and innovative methods are summarized. Ensuring appropriate thermal conditions for processing anthocyanin-rich food will allow a rational design for the future development of stable functional products, which retain these bioactive molecules and their functionalities to a great extent.